An analysis for service quality enhancement in electricity utility sector of India by SEM. Issue 6 (23rd August 2014) - Satapathy, Suchismita
Abstract : Purpose: The purpose of this paper is to develop a new model - namely service quality enhancement - in the electricity utility sector of south India and to test this model's fitness. Design/methodology/approach: Effective customer satisfaction investigation is a very important precondition for a power supply enterprise to win in the market competition. The problems that need to be solved for the power supply enterprise are how to use advanced and practiced methods to evaluate electricity customer satisfaction, and how to use results of the evaluation to improve their service. Planning and operating modern electric power systems involves several interlinked and complex tasks. In this paper, structural equation modeling is applied to the electricity utility service model to verify service quality satisfaction. To determine the scope of the electricity industry and its relationship with overall service quality, a questionnaire-based survey was conducted and a standard questionnaire was designed for all customers in different groups of stakeholders (i.e., domestic, industrial, agricultural, public organization). To investigate the respondents' perceptions regarding the service quality of the electricity utility industry, two hundred questionnaires were sent, and from these 169 responses were collected, consisting of 53 responses from the domestic sector, 43 industrial, 30 agricultural, and the remaining 43 from public organization consumers. Then a model was constructed using structural equation modeling and tested by Amos 18 to verify the casual relationship between the measured dimensions and the electricity service quality. Findings: The results indicate that electricity service has a direct relationship with the dimensions of reliability, tangibility, empathy responsiveness, assurance, security and stability. Originality/value: In this era electricity is the vital need, but due to regular interruptions in the electricity service, customer dissatisfaction is the measured issue. At the current time, the Indian electricity utility sector enjoys a monopolistic business. Therefore, there is hardly any effort to improve the service quality in this sector due to a lack of administrative pressure and reformation measures. Indian electricity consumers face many quality-related problems as far as the distribution of electricity is concerned. In order to assess service quality in electricity distribution, a survey has been conducted in this work to extract quality constructs from a customer's perspective. One of the contributions of this work is that on the basis of results obtained from factor analysis of the survey data, an instrument has been proposed for the first time in the Indian context, consisting of seven dimensions (reliability, tangibility, empathy, responsiveness, assurance, security and stability). This instrument would help to measure the service quality of the Indian electricity utility sectors, and it provides insights for managers and administrators to set a service standard to fill the service gap. Structural Equation Modeling (SEM) is a tool is used for confirmatory and exploratory factor analysis. It is used to test and validate standard instruments. Through confirmatory and exploratory factor analysis using SEM, the proposed service quality model has been tested and validated for practical acceptance in Indian electricity industry.